2019
DOI: 10.1039/c8nr08109c
|View full text |Cite
|
Sign up to set email alerts
|

Neoadjuvant nano-photothermal therapy used before operation effectively assists in surgery for breast cancer

Abstract: The neoadjuvant nano-photothermal therapy used before operation could shrink the tumor in a short time and make the boundary clearer, thus greatly assisting subsequent surgery resection and improving the surgery effect finally.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 35 publications
0
15
0
Order By: Relevance
“…Magnetic fluid hyperthermia as a special physical way,which could increase the temperature above 42°C and targeted to various tumor cells and tissues, has gained more and more attention and recognition 18. Superparamagnetic iron oxide nanoparticles have been widely used in imaging, drug delivery and heating,27,28 and their combination with surgery, radiotherapy, chemotherapy and even ultrasound29 has shown excellent outcomes in both in vitro and in vivo experiments on liver,30,31 breast,3235 colon3639 and brain cancers 4043…”
Section: Discussionmentioning
confidence: 99%
“…Magnetic fluid hyperthermia as a special physical way,which could increase the temperature above 42°C and targeted to various tumor cells and tissues, has gained more and more attention and recognition 18. Superparamagnetic iron oxide nanoparticles have been widely used in imaging, drug delivery and heating,27,28 and their combination with surgery, radiotherapy, chemotherapy and even ultrasound29 has shown excellent outcomes in both in vitro and in vivo experiments on liver,30,31 breast,3235 colon3639 and brain cancers 4043…”
Section: Discussionmentioning
confidence: 99%
“…[183,244,[318][319][320][321][322][323] Compared with conventional radiotherapy, PTT has the advantage in specificity without radiation and can potentially be an alternative to radiotherapy. [183,244,[318][319][320][321][322][323] Compared with conventional radiotherapy, PTT has the advantage in specificity without radiation and can potentially be an alternative to radiotherapy.…”
Section: Synergistic Surgery With Pttmentioning
confidence: 99%
“…[321] Compared with intraoperative PTT that is mainly applied to eliminate MRDs for improving surgical outcomes, neoadjuvant NPTT reduces tumors to facilitate subsequent resection, thereby possibly providing cancer patients who were previously evaluated to be inoperable with additional chances of resection surgery, as well as boosted surgical outcomes. [321] Compared with intraoperative PTT that is mainly applied to eliminate MRDs for improving surgical outcomes, neoadjuvant NPTT reduces tumors to facilitate subsequent resection, thereby possibly providing cancer patients who were previously evaluated to be inoperable with additional chances of resection surgery, as well as boosted surgical outcomes.…”
Section: Synergistic Surgery With Pttmentioning
confidence: 99%
“…Results showed that tumors could be eliminated completely under the high effective and precise dual‐mode hyperthermia under the guidance of tri‐modality imaging (i.e., photoacoustic/near‐infrared fluorescence/magnetic resonance) (see Figure 19D). Kang and co‐workers [ 155 ] further developed another optical‐magnetic nanoplatforms (MNP@PES‐dye800/FA) for preoperative nano‐photothermal therapy (NPTT) and assist in the follow‐up surgery under the tri‐modality molecular imaging guidance. Contributed by the adjuvant effect of preoperative NPTT, the tumor boundary is more clear for surgical resection, then leading to a better survival rate of tumor‐bearing mice models.…”
Section: The Applications Of Fmions In Cancer Theranosticsmentioning
confidence: 99%